2017
DOI: 10.1097/qad.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of simian immunodeficiency virus reservoirs in the brain of virally suppressed macaques

Abstract: Objective:Resting CD4+ T cells have been recognized as the major cell reservoir of latent HIV-1 during antiretroviral therapy (ART). Using an simian immunodeficiency virus (SIV)/macaque model for AIDS and HIV-related neurocognitive disorders we assessed the contribution of the brain to viral latency and reactivation.Design:Pigtailed macaques were dual inoculated with SIVDeltaB670 and SIV17E-Fr and treated with an efficacious central nervous system-penetrant ART. After 500 days of viral suppression animals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 41 publications
5
121
0
Order By: Relevance
“…Ingenol-3-mebutate (also known as ingenol-3-angelate) is FDA-approved as a topical therapy for actinic keratosis(49) and has demonstrated efficacy in multiple HIV-1 latency systems(46; 50). Ingenol B has recently been administered to non-human primates in combination with vorinostat (51). One of the two rhesus macaques exposed to ingenol B and vorinostat demonstrated increased SIV viral loads in both the central nervous system (CNS) and the periphery in response to LRA treatment, and also developed markers of systemic and CNS inflammation.…”
Section: T Cell Activating Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingenol-3-mebutate (also known as ingenol-3-angelate) is FDA-approved as a topical therapy for actinic keratosis(49) and has demonstrated efficacy in multiple HIV-1 latency systems(46; 50). Ingenol B has recently been administered to non-human primates in combination with vorinostat (51). One of the two rhesus macaques exposed to ingenol B and vorinostat demonstrated increased SIV viral loads in both the central nervous system (CNS) and the periphery in response to LRA treatment, and also developed markers of systemic and CNS inflammation.…”
Section: T Cell Activating Agentsmentioning
confidence: 99%
“…One of the two rhesus macaques exposed to ingenol B and vorinostat demonstrated increased SIV viral loads in both the central nervous system (CNS) and the periphery in response to LRA treatment, and also developed markers of systemic and CNS inflammation. A recent in vitro study of the effects of prostratin and bryostatin-1 on the central nervous system (CNS) identified that these agents may impair the integrity of the blood-brain barrier and increase trafficking of pro-inflammatory immune cells into the CNS(52), which may help to explain the results of the study by Gama and colleagues(51). …”
Section: T Cell Activating Agentsmentioning
confidence: 99%
“…However, to our knowledge, no single intervention to date has resulted in a significant reduction of the viral reservoir in vivo while various adverse effects have been observed (62,63). Of particular concern is the observation that some LRAs could disrupt the blood brain barrier and induce hyperinflammation of neural tissue, which has been shown to correlate with HIV-1 progression (64,65). Additionally, some HDACi impair HIV-specific CD8 T cell function as measured by a reduced capacity to eliminate HIV-1-infected cells (66).…”
Section: Discussionmentioning
confidence: 99%
“…Compare to chemical activating agents, CRISPR/Cas9 system is safer and more efficient though, the balance of "shock" and "kill" is difficult to master. A recent study reveals a severe inflammatory response in central neural system after chemical activation of simian immunodeficiency virus (SIV) reservoirs in the pigtailed macaques (ongoing HAART) [30]. Therefore, the clinical application should be considered deliberately to avoid catastrophic consequence of extensive activation without proper eradication.…”
Section: Methods For Eradicating Hiv Reservoirs Activating Then Elimimentioning
confidence: 99%